Hybrid Trade Fairs as Syncretic Format of Business Meetings at Boundary between Reality and Cyberspace – Possible Research Directions in Post-Pandemic Times - Marcin GEbarowski (Communications of International Proceedings, 2021)
Trade fairs have undergone a long-term evolution – from primary markets to the format known today, that is to say, entailing the exhibition of products at booths and face-to-face discussions. Exhibition events take more and more frequently a syncretic form of so-called hybrid trade fairs, which is mainly due to restrictions placed on personal meetings during the COVID-19 pandemic. However, extensive scholarly output relating to exhibition events does not include any publications on the format of trade fairs in question. Therefore there is a research gap. And it is expected that filling that gap will provide a starting point for this article, which aims to identify possible directions of scholarly research into the hybrid trade fairs. The aforesaid aim was accomplished based on a literature review and qualitative study – interviews with experts representing the Polish exhibit industry. The exploration indicated the need for researching hybrid trade fairs, specifically, in the following contexts: concerns over additional digital communication; advantages seen by exhibitors and visitors from various market areas; ability to build business relations; engagement of visitors and providing them with experiences.
Keywords: hybrid trade fairs; trade fair history; cyberspace; COVID-19 pandemic.